Bacterial loads and antibiotic resistance profile of bacteria isolated from the most popular street food (Phuchka) in Bangladesh - Hasan, Mahadi; Siddika, Farzana; Kallol, Md Arefin; Sheikh, Najibullah; Hossain, Muhammad Tofazzal; Alam, Md Mahmudul; Rahman, Marzia (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Phuchka is one of the most common street foods in Bangladesh. It is served with salad, sweet and sour tamarind dispersed water, and minced eggs as topping at places where people usually gather. This makes these foods susceptible to bacterial contamination. Therefore, assessing the bacterial load and antimicrobial profile of organisms isolated from phuchka and other foodstuffs served with it was the focus of this study. Materials and Methods: Bacterial isolates were isolated and identified from the samples after the bacterial loads were assessed as total viable count (TVC), total coliform count (TCC), and total staphylococcal count (TSC). The antibiotic resistance profile of the isolates was obtained using the disk diffusion method. Molecular detection of Escherichia coli isolates and the presence of gene responsible for tetracycline resistance was confirmed by polymerase chain reaction. Results: According to the recommendations, the TVC value of 70% phuchka and egg samples was safe, whereas TSC value illustrated that 80% of both phuchka and egg samples were at safety level. For the TCC value, 80% egg and 70% phuchka samples were found to be safe for consumption. Among all the samples, the microbial loads of the vendors’ hand wash were least in the safety level. Antibiotic sensitivity tests revealed that both Staphylococcus spp. and E. coli isolates were sensitive to gentamicin and ciprofloxacin but showed resistance to ampicillin. Conclusion: The data of this study indicate that phuchka can pose a public health problem as foodborne bacterial isolates which are antibiotic-resistant are found in it. J. Adv. Vet. Anim. Res., 8(3): 361-366, September 2021 http://doi.org/10.5455/javar.2021.h523